106 international cartoonists : exhibition - Rogers, Deidre S (1981)
Abstract art in black, red, white and green Poster advertising exhibition of 106 international cartoonists, held at the House of Humour and Satire, Gabrovo, in honour of 1300 years of the Bulgarian State PO-0215